Islamisasi Ilmu Pengetahuan Menurut Pandangan Syed Muhammad Naquib Al-Attas Dan Implikasinya Terhadap Pengembangan PAI Di Perguruan Tinggi Umum - Muhammad Sayyidul Abrori; Muhammad Nurkholis (JURNAL PENDIDIKAN ISLAM AL I’TIBAR, 2019)
This abstract contains aboutthe Islamic concept of science according to al-Attas that the biggest challenge facing Muslims isthe challenge of knowledge spread throughout the Islamic world by Western civilization.Islamization of knowledge means Islamizing or purifying Western product science which has been developed and used as a reference in the development discourseIslamic education system in order to obtain a "typical Islamic" science. Al-Attas defines science as a meaning that comes into the soul along with the coming of the soul to the meaning and producing the desire and will of self. Al-Attas defines the meaning of education as a process of planting something into human beings and then affirms that something that is implanted is a science, and the purpose in seeking this knowledge is contained in the concept of ta'dib.While the aim of Islamic education is to instill virtue in "human self" as an individual and as part of society. Islamic education is capable Ideally, Naquib wants to print a good human being universally (al-insan al-kamil). The implication in the development of Islamic education in PTU is that Islamic education is directed at producing quality human resources, quality in the intellectual field and the most fundamental are moral and religious values.